Increased cyclooxygenase-2 and vascular endothelial growth factor protein expression is associated with canine prostatic carcionogenesis process - Amorim, Renee Laufer [UNESP]; Fonseca-Alves, Carlos Eduardo [UNESP]; Tivera Calderon, Luis Gabriel [UNESP]; Justo, Andre Augusto [UNESP]; Rogatto, Silvia Regina [UNESP] (Amer Assoc Cancer Research, 2014)
Background: COX-2 is one of the most important prostaglandin involved in urologic cancer and seems to be associated with tumor progression, invasion, and metastasis. In addition, several effects have been reported for VEGF, including inducing angiogenesis, promoting cell migration, and inhibiting apoptosis. COX2 and VEGF up-regulation have been reported in human prostate cancer. Due to the importance of canine natural model for prostate cancer, the aim of this study was to evaluate COX-2 and VEGF protein expression in canine carcinogenic process. Material and Methods: Seventy-four prostatic tissues from dogs were selected to be evaluated for protein expression by immunohistochemistry (IHC), including: 10 normal prostatic tissues, 20 benign prostatic hyperplasias (BPH), 25 proliferative inflammatory atrophies (PIA) and 20 prostatic carcinomas (PCa). COX-2 and VEGF were detected using the monoclonal antibody CX-294 (1:50 dilution, Dako Cytomation and sc-53463 (1:100 dilution, Santa Cruz), respectively. The immunolabelling was performed by a polymer method (Histofine, Nichirei Biosciences). All reaction included negative controls by omitting the primary antibody. The percentage of C-MYC, E-cadherin, and p63- positive cells per lesion was evaluated according to Prowatke et al. (2007). The samples were scored separately according to staining intensity and graded semi-quantitatively as negative, weakly positive (1), moderately positive, and strongly positive. The score was done in one 400 magnification field, considering only the lesion, since this was done in a TMA core of 1 mm. For statistical analyses, the immunostaining classifications were reduced to two categories: negative and positive. The negative category included negative and weakly positive staining. Chi-square or Fisher exact test was used to determine the association between the categorical variables. Results: The COX-2 protein expression was elevated in the cytoplasm of the canine PCa and PIA compared to normal prostate (p=0.002). VEGF protein expression was increased in 94.75% of the PCa and 100% of the PIA compared with to normal prostate (p = 0.001). No difference was found when compared normal prostate with BPH. Conclusions: This study has demonstrated that the carcinogenesis of canine prostatic tissue may be related to gain of COX-2 and VEGF protein expression.